IMPACT OF SHALE HETEROGENEITY ON SORPTION CAPACITIES IN THE LIMESTONE GREEK WELL, MARCELLUS SUBGROUP, WESTERN PART OF NEW YORK STATE, UNITED STATES OF AMERICA - MOHAMMEDALI, SHAMA MOHAMMED BALULLA (2018)
Organic–rich shales comprise significant resources of natural gas, which occurs as free, dissolved and adsorbed gas. Understanding the relative proportions of gas stored in these different forms is important for an accurate assessment of the Original Gas In Place (OGIP). However, despite the increased importance of sorbed gas, uncertainties remain regarding controls on gas sorption capacity by lithological variations as well as critical shale geochemical and petrophysical properties.